A Friendly Critique of ‘Asian Criminology’ and ‘Southern Criminology’ - Moosavi, Leon (The British journal of criminology, 2019)
Like all other social sciences, criminology is characterized by an ethnocentrism that often excludes non-Western scholarship. ‘Asian criminology’ and ‘Southern criminology’ are relatively new paradigms that seek to rectify this by problematizing criminological knowledge production and incorporating marginalized perspectives. Despite both projects sharing commonalities, they have not been comprehensively discussed alongside each another. This article offers a robust yet ‘friendly’ critique of both paradigms in order to overcome the lack of theoretical interrogation that they have faced. It is argued that Asian criminology and Southern criminology could ‘decolonize criminology’ if they are able to overcome the specific limitations that are identified within this article.